Gender and innovation processes in integrated fish agri-food systems in Bangladesh and the Philippines: Insights from the CGIAR Research Program on FISH - Aregu, Lemlem; Farnworth, Cathy Rozel; Choudhury, Afrina; Rajaratnam, Surendran; McDougall, Cynthia (WorldFish, 2018)
This FISH report provides insights on the interactions between gender norms, agency, and innovation in fish agri-food systems.